Ответ:
Объяснение:
R = R1 + (R2*R3 / (R2+R3))
R = U^2 / P
R1 + (R2*R3 / (R2+R3)) = U^2 / P
60 + (50*R3 / (50+R3)) = 100^2 / 100
40 = 50*R3 / (50+R3)
2000 + 40*R3 = 50*R3
R3 = 200 Ом
I = I1 = P/U = 100 / 100 = 1 A
U1 = I*R1 = 1 * 60 = 60 B
U2=U3 = U - U1 = 100-60 = 40 B
I2 = U2 / R2 = 40 / 50 = 0.8 A
I3 = I1 - I2 = 1 - 0.8 = 0.2 A
P1 = I1*U1 = 1*60 = 60 Вт
P2 = I2*U2 = 0.8*40 = 32 Вт
P3 = I3*U3 = 0.2*40 = 8 Вт
P = P1+P2+P3
100 = 60 + 32 + 8
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
R = R1 + (R2*R3 / (R2+R3))
R = U^2 / P
R1 + (R2*R3 / (R2+R3)) = U^2 / P
60 + (50*R3 / (50+R3)) = 100^2 / 100
40 = 50*R3 / (50+R3)
2000 + 40*R3 = 50*R3
R3 = 200 Ом
I = I1 = P/U = 100 / 100 = 1 A
U1 = I*R1 = 1 * 60 = 60 B
U2=U3 = U - U1 = 100-60 = 40 B
I2 = U2 / R2 = 40 / 50 = 0.8 A
I3 = I1 - I2 = 1 - 0.8 = 0.2 A
P1 = I1*U1 = 1*60 = 60 Вт
P2 = I2*U2 = 0.8*40 = 32 Вт
P3 = I3*U3 = 0.2*40 = 8 Вт
P = P1+P2+P3
100 = 60 + 32 + 8